Report of a Coarctation of Aorta Stenting in an Infant - Mehdi Ghaderian; Mohammad Reza Sabri (Advanced Biomedical Research, 2019)
Coarctation of aorta (CoA) is a congenital heart disease that can lead to heart failure during infancy and neonatal period. Several treatments have been proposed for this disease, including surgery and balloon angioplasty. The experiences of using stents in small infants or neonatal patients are very low. In this article, we report a 3 months old age infant who after balloon angioplasty, his CoA symptoms had return and stenting of CoA was performed for him.